Giovanni Klaus Koenig Un fiorentino nel dibattito nazionale su architettura e design (1924-1989) - Tonelli, Maria Cristina (Studi e saggi, 2020)
An architect and academic, Giovanni Klaus Koenig (1924-1989) was a designer of rail means of transport, passionate scholar of trains and trams, critic of contemporary architecture and an industrial design historian. As an intellectual he was committed to solving the problems of Florence, his city. All of this in years in which critical and operational attention to the present was uncommon, the discipline of design was still to be founded, the involvement of an architect with rolling stock companies was out of the ordinary. The text aims to piece together his figure mirrored with his city and the national context, thanks to the contribution of those who had him as an interlocutor and the scholars who worked on the beaten track of his research. The goal is not limited to render the complex of a culturally incisive personality, but to highlight areas still to be explored for current scholars, those "phosphorescent trails" that he left us as a legacy.